1999
DOI: 10.1093/oxfordjournals.jbchem.a022376
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Mechanical Stress Induces Extracellular Matrix Degradation in Cultured Chondrocytes via Gene Expression of Matrix Metalloproteinases and Interleukin-1

Abstract: To clarify the mechanism of cartilage degradation induced by mechanical stress, we investigated the influence of cyclic tension force (CTF) on the metabolism of cultured chondrocytes. The chondrocytes were exposed to CTF using a Flexercell strain unit. Five or 15 kPa of high frequency CTF significantly inhibited the syntheses of DNA, proteoglycan, collagen, and protein. Fifteen kPa of high frequency CTF induced the expression of interleukin-1 (IL-1), matrix metalloproteinase (MMP)-2 and -9 mRNA, and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 0 publications
4
109
1
Order By: Relevance
“…We found that mechanical strain loaded on the chondrocytes clearly enhanced ROS production. It is worth noting that Fujisawa et al reported enhanced production of interleukin-1 (IL-1) with cyclic tensile stretch using chondrocytes (15). It is well accepted that chondrocytes possess an NADPH oxidase and produce ROS (16).…”
Section: Discussionmentioning
confidence: 99%
“…We found that mechanical strain loaded on the chondrocytes clearly enhanced ROS production. It is worth noting that Fujisawa et al reported enhanced production of interleukin-1 (IL-1) with cyclic tensile stretch using chondrocytes (15). It is well accepted that chondrocytes possess an NADPH oxidase and produce ROS (16).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biomechanical forces such as tension, compression and shear have been shown to modulate the activity of MMP-2 in chondrocytes (Fujisawa et al, 1999), ligaments (Zhou et al, 2005), muscle (O'Callaghan and Williams, 2000;Auluck et al, 2005) and in the cardiovascular system (Milkiewicz et al, 2005;Rastogi et al, 2005).…”
Section: Effect Of Equibiaxial Stretch On Mmp-2 Activitymentioning
confidence: 99%
“…The results of our study raise the question of whether cartilage of the hip joints may be even more sensitive to IL-1␤ stimulation. It has also been reported that excessive and continuous mechanical stress induces production of IL-1␤ by chondrocytes (34). Hip joints are subjected to especially high (multiplied) load stresses during normal walking, due to the femoral neck/lever arm effect counterbalanced by the force exerted by the abductor muscles (35).…”
Section: Il-1 Gene Cluster Polymorphisms and Pathogenesis Of Hip Oamentioning
confidence: 99%